Hubungan Anemia Defisiensi Besi dengan Risiko Infeksi Saluran Pernapasan Berulang pada Anak: Literature Review - Afiyah Salsabila Ilyas; Nadirah Rasyid Ridha; Nur Aisyah (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Iron deficiency anemia (IDA) is a condition of insufficient iron that lowers hemoglobin levels and disrupts erythrocyte formation. This condition commonly occurs in children and can weaken the immune system, thereby increasing the risk of recurrent respiratory tract infections such as bronchiolitis, pneumonia, and Acute Respiratory Tract Infections (ARTI). Children with IDA are also at risk of worsening clinical conditions. This study employed a literature review method with a descriptive-analytical approach. A total of 10 journals (2020–2026) from Google Scholar, PubMed, ResearchGate, Elsevier, and the National Center for Biotechnology Information (NCBI) were analyzed using the Population, Intervention, Comparison, Outcome, Study Design (PICOS) framework and synthesized narratively. The results of the review indicate that iron deficiency anemia is significantly associated with an increased risk of recurrent respiratory tract infections in children. Children with IDA have a 2–5 times higher risk of developing bronchiolitis and pneumonia, and up to 10 times greater susceptibility to recurrent ARTI. This condition is also associated with increased disease severity, characterized by low hemoglobin levels, mean corpuscular volume (MCV), and serum iron, as well as elevated total iron-binding capacity (TIBC). Iron supplementation has been proven effective in reducing the incidence of recurrent infections. In conclusion, iron deficiency anemia is associated with an increased risk and severity of recurrent respiratory tract infections in children. Early detection and iron supplementation are essential to reduce morbidity and prevent infection recurrence.